The wound/burn guidelines – 1: Wounds in general. Issue 4 (12th March 2016) - Inoue, Yuji; Hasegawa, Minoru; Maekawa, Takeo; Le Pavoux, Andres; Asano, Yoshihide; Abe, Masatoshi; Ishii, Takayuki; Ito, Takaaki; Isei, Taiki; Imafuku, Shinichi; Irisawa, Ryokichi; Ohtsuka, Masaki; et al.
Abstract: The Japanese Dermatological Association determined to prepare the Wound/Burn Guidelines focusing on treatments, catering to needs for the clinical practice of dermatology. Among these guidelines, "Wounds in General" was intended to explain knowledge necessary "to heal wounds" without specifying particular disorders.